Planning a Clinical Development Programme for Medicines for Bronchial Asthma - E. S. Petrova; D. V. Goryachev; A. D. Kuznetsova (Регуляторные исследования и экспертиза лекарственных средств, 2021)
The need for development of a clinical trial guidance for medicines for bronchial asthma is brought about by the improvement of requirements for research programmmes for new medicines. The aim of the study was to develop a methodological approach to conducting clinical trials of bronchial asthma medicines in Russia in line with the existing international requirements. The authors analysed regulatory documentation on the development of medicines for treatment of bronchial asthma in adults taking into account the current clinical guidelines, and specific aspects of developing medicines for treatment of bronchial asthma in children. The paper also analyses some clinical research aspects related to the development of immunotherapy. The analysis of up-to-date Russian and international clinical guidelines for bronchial asthma treatment, which are focused on bronchial asthma managementusing basic therapy, revealed the need to use revised disease concepts and new criteria to assess the efficacy of asthma medicines. The authors formulated consistent approaches to planning a clinical development programme for medicines for bronchial asthma, and suggested methodology for conducting clinical research based on recommendations of the European Medicines Agency.